ISLAM RAHMATAN LIL ALAMIN FROM SOCIAL AND CULTURAL PERSPECTIVE - Muhammad Khairan Arif (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2021)
Rahmatan Lil Alamin's Islamic is a general purpose of Islam (Maqashid Am Li Syariah). All the teachings of Islam boil down to Maslahat, compassion and peace of the world, beings and all human beings. The purpose of this study is to uncover the characteristics and main objectives of Islamic teachings that rahmatan lil alamin in the social and cultural life of modern humans. The method used in this study is the Method of Literature Study and analysis of scientific references related to Islam rahmatan lil alamin in social and cultural perspectives. the result of this kajia is that the implementation of Rahmatan Lil alamin values in social life can be seen in the educational life of schools, communities, places of worship and workplaces and mass media. The implementation of Rahmatan Lilalamin values in budya life, can be seen from the Development of Science, Language, Ideology and Customs.